The Possible Role of Body Temperature in Modulating Brain and Body Sizes in Hominin Evolution - Lingam, Manasvi (Frontiers in Psychology, 2022)
A number of models have posited that the concomitant evolution of large brains and increased body sizes in hominins was constrained by metabolic costs. In such studies, the impact of body temperature has not been sufficiently addressed despite the well-established fact that the rates of most physiological processes are manifestly temperature-dependent. Hence, the role of body temperature in modulating the number of neurons and body size is investigated in this work by means of a simple quantitative model. It is determined that modest deviations in the body temperature (i.e., by a couple of degrees Celsius) might bring about substantive changes in brain and body parameters. In particular, a higher body temperature may prove amenable to an increase in the number of neurons, a higher brain-to-body mass ratio and fewer hours expended on feeding activities, while the converse applies when the temperature is lowered. It is therefore argued that future studies must endeavour to explore and incorporate the effects of body temperature in metabolic theories of hominin evolution, while also accounting for other factors such as foraging efficiency, diet and fire control in tandem.